PENGEMBANGAN DESAIN KATALOG DIGITAL GUNA MENINGKATKAN DAYA SAING UMKM KULINER - Hetty Karunia Tunjungsari; Presilla; Victoria Valencia (Jurnal Serina Abdimas, 2026)
This community service activity aims to support the development of micro, small, and medium enterprises (MSMEs) in the culinary sector, especially Aprilia Chiffon Cake located in Yogyakarta, through the creation and optimization of digital catalogs. Culinary MSMEs often face limitations in terms of digital marketing, especially in compiling interesting and informative promotional materials. To answer these challenges, the service team provides assistance to business actors in the form of training and direct practice related to the preparation of visual content, writing effective product descriptions, and the use of digital platforms such as social media and marketplaces. The method of implementing activities includes initial observation of partner needs, preparation of catalog concepts that are in accordance with the business identity, technical design training sessions using free applications such as Canva, and evaluation and revision of catalogs based on partner feedback. The results of the activity show that partners are able to produce attractive and representative digital catalogs, as well as understand the importance of visual consistency and product narrative in building brand image. The resulting digital catalog includes complete information regarding the variety of chiffon cake products, prices, composition, and ordering contacts. The direct impact of this activity is the increase in partners' confidence in marketing their products online as well as increasing the reach of promotions through digital media. This activity is expected to be a similar mentoring model for other culinary MSMEs in digital transformation efforts. ABSTRAK Kegiatan pengabdian kepada masyarakat ini bertujuan untuk mendukung pengembangan usaha mikro, kecil, dan menengah (UMKM) di bidang kuliner, khususnya Aprilia Chiffon Cake yang berlokasi di Yogyakarta, melalui pembuatan dan optimalisasi katalog digital. UMKM kuliner seringkali menghadapi keterbatasan dalam hal pemasaran digital, terutama dalam menyusun materi promosi yang menarik dan informatif. Untuk menjawab tantangan tersebut, tim pengabdi melakukan pendampingan kepada pelaku usaha dalam bentuk pelatihan dan praktik langsung terkait penyusunan konten visual, penulisan deskripsi produk yang efektif, serta penggunaan platform digital seperti media sosial dan marketplace. Metode pelaksanaan kegiatan meliputi observasi awal terhadap kebutuhan mitra, penyusunan konsep katalog yang sesuai dengan identitas usaha, sesi pelatihan teknis desain menggunakan aplikasi gratis seperti Canva, serta evaluasi dan revisi katalog berdasarkan umpan balik mitra. Hasil kegiatan menunjukkan bahwa mitra mampu menghasilkan katalog digital yang menarik dan representatif, serta memahami pentingnya konsistensi visual dan narasi produk dalam membangun citra merek. Katalog digital yang dihasilkan mencakup informasi lengkap mengenai variasi produk chiffon cake, harga, komposisi, dan kontak pemesanan. Dampak langsung dari kegiatan ini adalah meningkatnya kepercayaan diri mitra dalam memasarkan produknya secara online serta peningkatan jangkauan promosi melalui media digital. Kegiatan ini diharapkan dapat menjadi model pendampingan serupa bagi UMKM kuliner lainnya dalam upaya transformasi digital.